2020
DOI: 10.1002/dta.2776
|View full text |Cite
|
Sign up to set email alerts
|

Hematocrit, blood volume, and surface area of dried blood spots – a quantitative model

Abstract: The use of the dried blood spot (DBS) sampling technique has extended the scope of clinical research, particularly in children. The effects of different hematocrit levels (25–55%) and different blood volumes (7.5–30 μL) on the surface area of the blood spots were investigated using ImageJ® software. Variation in hematocrit levels between patients and inaccuracies in blood volumes applied to Guthrie cards can have a marked effect on analyte concentrations measured in DBS samples. The current study presents a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The influence of Hct in DBS testing has been discussed in detail and is considered as one of the most important issues in this field 6,18,19 . In 2019 the International Association for Therapeutic Drug Monitoring and Clinical Toxicology published a review for the development and validation of DBS‐based methods 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of Hct in DBS testing has been discussed in detail and is considered as one of the most important issues in this field 6,18,19 . In 2019 the International Association for Therapeutic Drug Monitoring and Clinical Toxicology published a review for the development and validation of DBS‐based methods 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas analytical procedures including one, 3,13 two, 14,15 The influence of Hct in DBS testing has been discussed in detail and is considered as one of the most important issues in this field. 6,18,19 In 2019 the International Association for Therapeutic Drug…”
Section: Authentic Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…As each collected sample is precious, the main focus of the HCT strategy should be on non‐destructive HCT determination. A simple option to estimate the HCT is to correlate the scanned surface area of the spot in combination to the known applied volume of whole blood 52 . A more advanced application of non‐destructive HCT measurement during an anti‐doping study has been presented by Lange et al using NIR 53 .…”
Section: Measurement Of Hct In Dbsmentioning
confidence: 99%
“…A simple option to estimate the HCT is to correlate the scanned surface area of the spot in combination to the known applied volume of whole blood. 52 A more advanced application of non-destructive HCT measurement during an anti-doping study has been presented by Lange et al using NIR. 53 However, they concluded that differences in temperature or humidity might influence the molecular vibrations of the DBS matrix, thus negatively influencing the outcome of the used DBS NIR spectrometry measurement.…”
Section: Measurement Of Hct In Dbsmentioning
confidence: 99%